Três espécies crípticas em Sturnira lilium (Chiroptera: Phyllostomidae) : evidências baseadas em genes mitocondriais - Dinelli, Lorena Luppe (2013)
TheNew World leaf-nosed bats of the genus Sturnirahasknowncomplex phylogenetic relationships due toincongruencebetweenmorphological and molecular data.Are recognized for the genus 14 species, among which is included Sturnira lilium, widelydistributedspecie, occurring from Mexico to Uruguay. Previously studies suggest thatS. liliumhasmorphological plasticity and therefore could represent more than one species.Thus, the present study aimed to evaluate the distribution of genetic diversity in a phylogenetic and geographic context in S. lilium, and discuss the possibility of cryptic species. Sequences from three mitochondrial markers, cytochrome oxidase I, COI (205 sequences), cytochrome b, Cyt b (172 sequences) and the mitochondrial DNA control region, D-loop (101 sequences) were used to infer phylogenies and demographic history in S. lilium. All results indicate a pattern of geographicalstructure ofgenetic diversity, with three major clades isolated byhigh divergence (5-8%).Clade I has northern distribution, including samples from Mexico and northern Central America.CladeIIincluded samples from Panama and northwestern South America separated into two minor groups with overlapping distribution and 2%of genetic divergence. Clade III hassoutherndistribution, including samples from Bolivia and eastern Brazil.Populations within each group showed little structure, evidenced by haplotype sharing between remote locations.There is geographical correlation between clades II and the Amazon biome and clade III and the Atlantic Forest biome. Ahypothesis for the evolution of these groups is the emergence of group III from a common northernancestor. This hypothesis is based on population demographics data indicating population stability in group II.Stability indicates an olderorigin for the group II while group III presents recent expansion.In addition, Brazil sequencescould contain pseudogenes. Pseudogenes are considered "genetic fossil" because of low variationfrom the original sequence, confirming the hypothesis of a northernancestral to clade III.Each clade canrepresents adistinct taxonomic unit based on Genetic Conceptof Species, since the genetic distances between thanare similarto those observed amongS. lilium and S. tildae